ELTV Channel 6 News (African Knowledges and the History Publication since the 1970s, 1988)
Planning celebration of the second anniversary of the inauguration of Samuel Kanyon Doe as the first president of the Second Republic of Liberia; food production in Liberia; education in Liberia.
Keywords: Education; Food Production